Building a peaceful society : creative integration of peace education - Finley, Laura L. (Peace education., 2011)
To truly move toward a more peaceful society, it is imperative that peace education better address structural and institutional violence. This requires that it be integrated into institutions outside of schools and universities. Doing so will be challenging, as many of these institutions are structured on domination and control, not on partnership and shared power. In particular, U.S. criminal justice, social services and prevention programs, and sport have tended to be dominator-modeled. This book offers analysis and suggestions for overcoming these challenges and for integrating peace education into important social institutions.Creativity will be one of the most useful assets in moving peace education from schools to other institutions. This book argues that with creative visioning, collaboration, and implementation, peace education can be integrated into the most challenging situations and provide hope for holistic changes in our society.